Walkability Index Pada Zona Komersial Melalui Segmentasi Area Trotoar di Kota Pekanbaru - Muchammad Zaenal Muttaqin; Siti Khodizah (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2021)
Walkability index is an assessment of pedestrians through the physical condition of a sidewalk facility. Sukaramai Plaza is located in the CBD (Central Business District) Area of Pekanbaru City. This area has become an attractions for the people of Pekanbaru and other areas. As for the movement that occurs not only the movement of vehicles in the lane of vehicles, but also pedestrians. Evaluation of pedestrian paths is needed to provide an input regarding the comfortability for pedestrian.  This study aims to evaluate the sidewalk in the Sukaramai Plaza area on Jalan Sudirman, Pekanbaru. Sidewalk in this area is divided by 4 segments. The parameters used are the physical condition for pedestrians about 9 parameters of the physical condition of the sidewalk for each segment. The results showed that sidewalk has a walkability score in the range of 50-70 which is a good enough category to walk. In addition, the results of this study also showed that the presence of a shop window above the sidewalk making difficult for pedestrian. Therefore, the results will contribute primarily to the pedestrian pathway provider and the government as a regulator to improve pedestrian facilities, especially in the city of Pekanbaru.